Effect of Deficit Irrigation on Yield and Quality of Eggplant - Darko, Ransford Opoku; Yuan, Shouqi; Kumi, Francis; Quaye, Frederick (International Journal of Environment, Agriculture and Biotechnology, 2019)
The aim of the study was to determine the effect of deficit irrigation on yield and quality of eggplant. Eggplant cultivated under different irrigation treatment. The treatment imposed included, treatment 1 (100ETc: full irrigation), treatment 2 (90ETc: 10% reduction of full irrigation), treatment 3 (80ETc: 20% reduction of full irrigation), treatment 4 (70ETc: 30% reduction of full irrigation). Eggplant cultivated under different irrigation treatment and were harvested and analyzed for total yield, fruit shape, pH of the fruit, moisture content, protein, carbohydrate, phosphorus. Deficit irrigation had significant effect on the protein content, carbohydrate content and fruit moisture. Results of the study showed that deficit irrigation had no significant effect on phosphorus and fruit shape. Also, deficit irrigation reduced disease incidence in eggplants while ensuring an improvement in fruit firmness and the overall marketable yield. The study concludes that a reduction of 10% ETc in the cultivation of eggplant would produce optimum and quality fruits thereby saving irrigation water.